2018
DOI: 10.1080/10641955.2018.1516225
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness during controlled ovarian hyperstimulation and early pregnancy in women exposed to assisted reproduction

Abstract: Introduction: Female sex hormones have vasorelaxing effects in non-pregnant and pregnant women. We aimed to investigate the effect of controlled ovarian hyperstimulation (COH) for in vitro fertilization (IVF), and early pregnancy, on arterial stiffness as assessed by digital pulse wave analysis (DPA), hypothesizing reduced arterial stiffness as an effect of increased estrogen levels. Material and methods: A total of 68 women undergoing IVF were examined with DPA before conception and during IVF treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Their outcomes recommend that the SDPPG-b/SDPPG-a index might be useful to identify high-risk subjects for cardiovascular heart disease. The SDPPG-b/SDPPG-a ratio increased with an increment of age [34,37]. The SDPPG-d/SDPPG-a ratio demonstrates the intensity of reflecting pulse waves from peripheral arteries [34].…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Their outcomes recommend that the SDPPG-b/SDPPG-a index might be useful to identify high-risk subjects for cardiovascular heart disease. The SDPPG-b/SDPPG-a ratio increased with an increment of age [34,37]. The SDPPG-d/SDPPG-a ratio demonstrates the intensity of reflecting pulse waves from peripheral arteries [34].…”
Section: Introductionmentioning
confidence: 89%
“…The SDPPG-b/SDPPG-a ratio increased with an increment of age [34,37]. The SDPPG-d/SDPPG-a ratio demonstrates the intensity of reflecting pulse waves from peripheral arteries [34]. Takazawa et al [35] revealed that the increasing SDPPG-d/SDPPG-a ratio represented a reduction of arterial stiffness; therefore, the SDPPG-d/SDPPG-a ratio decreased with increasing age and higher arterial stiffness [34,37].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations